THE ROLE OF DEMOGRAPHIC FACTORS MODERATING THE LEVEL OF DIGITAL LITERACY ON ONLINE LENDING BEHAVIOR - Tri Rachmat Riski; Henny Sulistianingsih; Maivalinda Maivalinda (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2024)
The aim of this study to explore the role of demographic factors moderating the level of digital literacy on online lending behavior. This study use a purposive sampling technique and the sample elements of the object are selected based on certain considerations and criteria, namely micro and small business actors on this study. Data was collected using survey techniques with a total of 100 respondents. The proposed model of this study are using descriptive analysis and SEM PLS in order to obtain the information about digital literacy on the online lending behavior of the Padang community moderated by demographic factors. The results of this study show that the majority of respondents are dominated by productive age who have high intensity in utilizing peer-to-peer lending (P2P lending) information technology. This study also shows the significance of financial literacy in influencing financial behavior, and the demographic factors are significantly able to moderate financial literacy on financial behavior. The study results also show that it is important for future researchers to make risk preferences and social environment a relevant approach in measuring individual financial behavior related to building a positive and wise perspective in using peer-to- peer lending (P2P lending). Keywords: Digital literacy, demographic factors, financial behavior, online lending